Glutathione and immune function - Dröge, Wulf; Breitkreutz, Raoul (Proceedings of the Nutrition Society, 2007)
The immune system works best if the lymphoid cells have a delicately balanced intermediate level of glutathione. Even moderate changes in the intracellular glutathione level have profound effects on lymphocyte functions. Certain functions, such as the DNA synthetic response, are exquisitely sensitive to reactive oxygen intermediates and, therefore, are favoured by high levels of the antioxidant glutathione. Certain signal pathways, in contrast, are enhanced by oxidative conditions and favoured by low intracellular glutathione levels. The available evidence suggests that the lymphocytes from healthy human subjects have, on average, an optimal glutathione level. There is no indication that immunological functions such as resistance to infection or the response to vaccination may be enhanced in healthy human subjects by administration of glutathione or its precursor amino acid cysteine. However, immunological functions in diseases that are associated with a cysteine and glutathione deficiency may be significantly enhanced and potentially restored by cysteine supplementation. This factor has been studied most extensively in the case of human immunodeficiency virus (HIV)-infected patients who were found to experience, on average, a massive loss of S equivalent to a net loss of approximately 4 g cysteine/d. Two randomized placebo-controlled trials have shown that treatment of HIV-infected patients with N-acetyl-cysteine caused in both cases a significant increase in all immunological functions under test, including an almost complete restoration of natural killer cell activity. It remains to be tested whether cysteine supplementation may be useful also in other diseases and conditions that are associated with a low mean plasma cystine level and impaired immunological functions.
Published online by Cambridge University Press: 28 February 2007
Reproduktion der Druck-Ausgabe
Gesehen am 03.02.2021